Transnationalism, Nationalism and Australian History
XIII, 199 p.
Keywords: In recent years History's ‘national narrative’ has been powerfully challenged by transnational and international debates. Using Australian history as a case study, this collection draws on leading contributions from academics and public intellectuals to explore the ways national identities still resonate in historical scholarship and reexamines key moments in Australian history, with a transnational lens, raising important questions about the unique context of Australia’s national narrative. The book examines the tension between national and transnational perspectives, attempting to internationalise the often parochial nation-based narratives that characterise national history, such as the history wars or the glorification of the Anzac Legend, whilst bearing in mind the limits of transnational histories in a national setting. Moving from the local and personal to the global, encompassing comparative and international research and drawing on the experiences of researchers working across nations and communities, this collection brings together diverging national and transnational approaches and asks several critical research questions: What is transnational history? How do new transnational readings of the past challenge conventional national narratives and approaches? What are implications of transnational and international approaches on Australian history? What possibilities do they bring to the discipline? What are their limitations? And finally, how do we understand the nation in this transnational moment?